Liberalization of the interurban coach market in Germany: Do attitudes and perceptions drive the choice between rail and coach? - Francisco J. Bahamonde-Birke; Uwe Kunert; Heike Link; Juan de Dios Ortúzar (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
In January 2013 the interurban passenger transport market in Germany was liberalized and several coach carriers emerged offering an alternative to the Deutsche Bahn, a state owned rail monopoly. The coach carriers have attempted to position themselves not just through lower prices but also through product differentiation, for example marketing their services as the most ecological way to travel. Hence, it is important to consider attitudes and perceptions when analyzing this market. One year after liberalization we conducted a stated-choice experiment among students and employees at the Technical University of Berlin, where participants had to choose between different interurban public transport alternatives (regional and intercity trains or interurban coaches). Additionally, the experiment gathered perception and attitudinal indicators used to construct latent variables. Our results show that attitudes and perceptions indeed affect the way individuals choose between different transport modes and, therefore, they must be taken into account when analyzing the interurban passenger market in Germany.
Keywords: R41; 330; Liberalization; Coach Market; Latent Variables; Hybrid Discrete Choice Modelling; Attitudes and Perceptions